2021
DOI: 10.1016/j.compscitech.2021.108735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interfacial fibre orientation and PPS veil density on delamination resistance of 5HS woven CFRP laminates under mode II loading

Abstract: This paper presents an experimental study on the effect of interfacial fibre orientation and interleaved thermoplastic veil on Mode II interlaminar fracture toughness of 5-harness satin woven carbon fibre reinforced polymer composite laminates. Three-point End-Notched Flexure tests were carried out to determine delamination resistance, GIIC of specimens with five fibre orientation biases and two veil densities at the midplane. Results show that delamination resistance of 5-harness satin woven laminates depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…In [ 8 ], resistance against delamination under Mixed-Mode loading (G II = 34%, 85%) was investigated for 0°//0°, 0°//22.5°, 0°//45°, and 0°//90° interfaces. More recent results of similar investigations can be found, e.g., in [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], and in [ 19 , 20 , 21 , 22 ] where also R-curves were of interest.…”
Section: Introductionmentioning
confidence: 58%
“…In [ 8 ], resistance against delamination under Mixed-Mode loading (G II = 34%, 85%) was investigated for 0°//0°, 0°//22.5°, 0°//45°, and 0°//90° interfaces. More recent results of similar investigations can be found, e.g., in [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], and in [ 19 , 20 , 21 , 22 ] where also R-curves were of interest.…”
Section: Introductionmentioning
confidence: 58%
“…The electrical resistance change method (ERCM) was reported to detect the damage of CFRP. [14][15][16][17][18][19] In previous studies, the ERCM has been used to detect cracking of laminate composites under tensile, 20 compression, 21 and bending. 22,23 Grammatikos and Paipetis 24 found that invisible crack caused the resistance to increase irreversibly under tensile.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang and Li 13 found that interfacial shear stresses caused the change of interfacial structure, and led to the change of resistance between single fiber and matrix under tensile.The electrical resistance change method (ERCM) was reported to detect the damage of CFRP. [14][15][16][17][18][19] In previous studies, the ERCM has been used to detect cracking of laminate composites under tensile, 20 compression, 21 and bending. 22,23 Grammatikos and Paipetis 24 found that invisible crack caused the resistance to increase irreversibly under tensile.…”
mentioning
confidence: 99%
“…Barely visible impact damage (BVID) is a perception which often neglects the underlying damage introduced within the laminate [1]. Impact energy can be absorbed at any point of the laminate, sometimes far from the impact site due to the inherent material characteristics and brittle nature of fibers and matrix [2]. Although impacting at low energy, there can be various levels of laminate failure mechanisms during energy absorption, including, front face indentation, interlaminar delamination, back face splitting, and fiber peeling [3].…”
Section: Introductionmentioning
confidence: 99%